Peran Mahasiswa Perguruan Tinggi Islam Aceh Tenggara sebagai Agents of Social Change - Sahipul Anwar; Sahidup Kudadiri; Candra Wijaya (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2019)
Higher education is obliged to carry out education, research and community service. Through the tridarma of higher education students must actually contribute to society. This research focuses on the role of Southeast Aceh university students as Agents of Social Change. This study uses qualitative research methods with a sociological approach. The results of this study indicate that students of Southeast Aceh Islamic tertiary institutions have played a positive role in the formation of people's lives and have a very important, strategic role in the formation of moral, moral and ethical learners who are currently at the lowest point in community development. The role of Islamic education is to create and create students who are characterized or Islamic in character, who are part of the community.